Fiscal Relations within the European Union - Hoeller, Peter (OECD Economics Department Working Papers, 1996)
This paper reviews fiscal relations within the European Union in the context of the theory of fiscal federalism and of the principle of subsidiarity. It analyses the fiscal policy implications of the introduction of the single currency, tax harmonisation and competition issues and spending at the EU level. It also speculates as to whether there are economic gains from centralising more expenditure functions at the EU level ...